MULTILINGUALISM AND ITS AFFECTS ON LEARNING A NEW LANGUAGE (Scientific journal of the Fergana State University, 2023)
In this paper, we try to research on the question if it is easier to acquire a new language if the language leaner is multilingual rather than monolingual language leaner. The questionnaire and interview research methods are utilized in order to gain effective and relevant results. From the research data, it can be concluded that in addition to mental relaxation, most languages ​​are lexically and grammatically close to each other and have many similarities, so this factor can create many conveniences for language learners in learning a new language.